PERAN KEARIFAN LOKAL DALAM MEMBANGUN CITRA RUMAH SAKIT : TINJAUAN LITERATUR SISTEMATIS - Rina Asih Budi Cahyaningrum Rina Asih Budi Cahyaningrum; Bayu Hartono; Intan Sekar Arumdani (Journal of Hospital Administration and Management (JHAM), 2026)
​​ This study analyzes hospital image through sustainable policies that integrate local wisdom and holistic care approaches. Local wisdom-based policies are considered capable of adapting services to the community's cultural values, whereas holistic care emphasizes comprehensive treatment encompassing physical, emotional, social, and spiritual aspects. A descriptive analysis based on the Scopus database reveals that research trends using the keywords "holistic AND care AND policy" peaked in 2024, with the United States dominating the research field. This topic involves several multidisciplinary perspectives, including managerial, social, cultural, and health aspects. The holistic care approach is regarded as a strategic dimension capable of providing added value to hospital services, thereby exerting a positive impact on public perception of health institutions. In conclusion, a positive hospital image can be built through strategies that integrate sustainable policies based on local wisdom and holistic care. This strategy not only supports the sustainability of hospital operations but also strengthens the emotional connection between the hospital and the community.